Physiological mechanism of melatonin attenuating to osmotic stress tolerance in soybean seedlings - Jahan, Mohammad Shah; Zhao, Chang Jiang; Shi, Li Bo; Liang, Xiu Ren; Jabborova, Dilfuza; Nasar, Jamal; Zhou, Xun Bo (Frontiers in Plant Science, 2023)
Soybean is a major legume crop with immense economic significance, but its production is highly dependent on optimum rainfall or abundant irrigation. As the global climate changes, it is more important to find solutions to make plants more resilient to drought. The prime aimed of the study is to investigate the effect of melatonin on drought tolerance in soybean and its potential mechanisms. Soybean seedlings were treated with 20% polyethylene glycol 6000 (PEG 6000) and subjected to osmotic stress (14 days) with or without 100 μM melatonin treatment. Our results revealed that melatonin supplementation significantly mitigated PEG-induced growth retardation and increased water absorption ability. Foliar application of melatonin also increased gas exchange and the chlorophyll fluorescence attributes by the mitigation of the osmotic-induced reduction of the reaction activity of photosystems I and II, net photosynthetic net (Pn), stomatal conductance (Gs), transpiration rate (Tr), electron transport activity, and photosynthetic efficiency. In addition, PEG-induced elevated production of reactive oxygen species (ROS) and malondialdehyde (MDA) content were significantly reversed by melatonin treatment. Equally important, melatonin boosted the antioxidant activities of soybean plants. Moreover, osmotic stress substantially increased abscisic acid (ABA) accumulation in roots and leaves, while melatonin-received plant leaves accumulated less ABA but roots content higher ABA. Similarly, melatonin significantly suppressed ABA biosynthesis and signaling gene expression in soybean exposed to drought stress. Furthermore, osmotic stress significantly suppressed plasmalemma (GmPIPs) and tonoplast aquaporin (GmTIPs) genes expression, and their transcript abundance was up-regulated by melatonin co-addition. Taken together, our results indicated that melatonin potentially improves drought tolerance of soybean through the regulation of ABA and aquaporin gene expression, increasing photosynthetic efficiency as well as enhancing water uptake efficiency.